COOPERATIVE LEARNING AND PRE-PROFESSIONAL PRACTICE LEARNING IN A UNIVERSITY IN LIMA - Menacho Vargas, Isabel; Veronika Ponce Tello, Patricia; Supo Condori, Felipe (Gênero & Direito, 2020)
The study had as a general objective to establish the relationship among cooperative learning and learning the Pre-Professional Practice course in students of the IX and X cycle of the Professional Academic School of Education. It was a basic type study, with a cross-sectional non-experimental design, of a correlational descriptive level, the population consisted of 122 students who take the Pre-Professional Practice course of the IX and X cycle of the 2015-I semester. The sample is of type non-census probability. Having used the survey and observation techniques as instruments, the cooperative learning questionnaire and a knowledge test of pre-professional practice were applied. The results were obtained using the statistical Spearman correlation coefficient, which concludes that there is a positive relationship among cooperative learning and learning of the Pre-Professional Practice course in students of the IX and X cycle of the Academic Professional School of Education.